Immoral misdemeanor incompatible with the continuation of work as a ground for termination of the employment contract at the initiative of the owner or authorized body - V. V. Sychova (Law and Safety)
The Constitution of Ukraine enshrines and guarantees the right to work as an opportunity to earn a living by work that a person freely chooses or agrees to. One of the guarantees of the inviolability of the right to work is the impossibility of unreasonable and arbitrary termination of the employment contract on the initiative of the owner or authorized body. Such a guarantee follows from the provisions of Art. 40 of the Labor Code of Ukraine, which outlines an exhaustive list of grounds for termination of the employment contract with the employee. Guaranteeing the right to work for certain categories of workers is no exception. Such a guarantee is expressed in the provisions of Art. 41 of the Labor Code of Ukraine, which provides an exhaustive list of additional grounds for termination of the employment contract at the initiative of the owner or authorized body with a certain category of employees under certain conditions. A separate category of employees, whose employment contract may under certain conditions be terminated at the initiative of the owner or authorized body, include employees who perform an educational function. In particular, paragraph 3 of Part 1 of Art. 41 of the Labor Code of Ukraine provides such an additional ground for termination of the employment contract, as the commission of an employee who performs educational functions, an immoral misdemeanor, incompatible with the continuation of this work. However, the legislator, enshrining this additional basis for equalization of the employment contract, does not specify the legal content of immoral misconduct, incompatible with the continuation of work, which creates difficulties in its substantive understanding and therefore significantly weakens the protection of labor rights of workers. Based on a comprehensive analysis of domestic legislation and a wide range of theoretical and legal approaches to understanding immoral misconduct, incompatible with the continuation of work, it is clarified the legal content of the concept and formulated its definition. Emphasis is placed on the inexpediency of outlining at the legislative level an exhaustive list of acts that should be regarded as immoral, given their evaluative nature. Particular attention was paid to the provisions of the draft Labor Code of Ukraine and a comparative analysis of the normative content of paragraph 5 of Part 2 of Art. 92 of the draft LC of Ukraine under paragraph 3 of Part 1 of Art. 41 of the Labor Code of Ukraine. The peculiarities of the legal regulation of the termination of the employment contract under paragraph 3 of Part 1 of 41 Article of the Labor Code of Ukraine are highlighted and generalized, which are as follows: a) immoral misconduct is an evaluative concept that is not specified at the legislative level, and therefore, the establishment of its existence is carried out in each case, taking into account all the circumstances of the case; b) dismissal for committing an immoral misdemeanor is possible if such misdemeanor is incompatible with the continuation of work; c) the subject of dismissal may be an employee who performs the labor function of education; d) termination of the employment contract on the specified grounds is not a measure of disciplinary action and can be carried out only if there are specific facts that confirm the immoral behavior of the employee.